2019
DOI: 10.25077/mka.v42.i3s.p11-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan asupan vitamin D dengan kadar 25(OH)D serum pada ibu hamil trimester III etnis minangkabau

Abstract: Tujuan: Untuk mengetahui hubungan asupan vitamin D dengan kadar 25(OH)D serum pada ibu hamil trimester III etnis Minangkabau. Metode: Penelitian dengan desain cross-sectional di wilayah kerja Puskesmas Andalas Padang terhadap 88 orang subjek ibu hamil trimester III etnis Minangkabau. Penelitian dilakukan dengan teknik wawancara terstruktur menggunakan kuesioner dan food recall 24 jam selama dua hari dan pemeriksaan kadar 25(OH)D serum dengan metode ELISA. Hasil: Hampir separuh subjek penelitian (n=40; 45,5%) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…Other characteristics of subjects are presented in Table 1. We have previously reported that the dietary vitamin D intake in our subjects was not statistically significantly correlated with their levels of serum 25(OH)D [29].…”
Section: Resultscontrasting
confidence: 55%
“…Other characteristics of subjects are presented in Table 1. We have previously reported that the dietary vitamin D intake in our subjects was not statistically significantly correlated with their levels of serum 25(OH)D [29].…”
Section: Resultscontrasting
confidence: 55%